The pharmacokinetics of a slow-release theophylline preparation in horses after intravenous and oral administration - Errecalde, Jorge Oscar (1992)
The pharmacokinetics of a slow-release theophylline formulation was investigated following intravenous and oral administration at 10 mg/kg in horses. A tricompartmental model was selected to describe the intravenous plasma profile. The elimination half-life (t1/2β) was 16.91 ± 0.93 h, the apparent volume of distribution (Vd) was 1.35 ± 0.18 L/kg and the body clearance (ClB) was 0.061 ± 0.009 L kg−1 h. After oral administration the half-life of absorption was 1.24 ± 0.30 h, and the calculated bioavailability was above 100%. Thet1/2β after oral administration was 18.51 ± 1.75 h, only a little longer than that after intravenous administration. The slow release formulation did not exhibit any advantage in prolonging thet1/2β of theophylline in the horse.